New pages of the history of national librarianship - I. V. Lizunova; A. S. Metel'kov (Библиосфера, 2018)
The paper includes speeches of the participants of discussion platform «Independent book publishing: realities, prospects for the future»: theorists and practitioners of books-publishers - writers, poets, editors, kulturträgers, bibliologists. This article describes different points of view on the problems and prospects of developing the independent book publishing in various Russian regions and in the world. It emphasis on the history of the independent book publishing in Russia and Germany, new opportunities emergence for independent authors’ expressions: online publications, electronic publications, etc. Particular attention is paid to discussing the definitions, what is meant by «independent publishing», «self-publication», «self-edition», «self-printing», «self-editor», «kulturträge», «zine culture». The central topic of discussion was the problem of determining the quality of literature, self-promoting publications and distribution of professionals’ published books: bookselling network, social media, activity profitability, etc. Participants attempted to identify the place of Siberian independent publishers in the all-Russian and international publishing space, prospects for further development of independent book publishing in Siberia.